2006
DOI: 10.2337/db05-1433
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Pathway Inhibition Improved Vascular and C-Fiber Functions, Allowing for Pressure-Induced Vasodilation Restoration During Severe Diabetic Neuropathy

Abstract: Pressure-induced vasodilation, a neurovascular mechanism relying on the interaction between mechanosensitive Cfibers and vessels, allows skin blood flow to increase in response to locally nonnociceptive applied pressure that in turn may protect against pressure ulcers. We expected that severe neuropathy would dramatically affect pressure-induced vasodilation in diabetic mice, and we aimed to determine whether pressure-induced vasodilation alteration could be reversed in 8-week diabetic mice. Control and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…Diabetes was induced by both high and low STZ treatment with similar results (Table 3). Decreased motor [61][62][63] and sensory [62,64] nerve conduction velocities are reported following 8-36 weeks of diabetes. Studies vary in the response to a thermal stimulus.…”
Section: Mouse Models Of Dnmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes was induced by both high and low STZ treatment with similar results (Table 3). Decreased motor [61][62][63] and sensory [62,64] nerve conduction velocities are reported following 8-36 weeks of diabetes. Studies vary in the response to a thermal stimulus.…”
Section: Mouse Models Of Dnmentioning
confidence: 99%
“…Studies vary in the response to a thermal stimulus. Arrieta et al [65] report thermal allodynia 12 weeks post STZ-treatment while Demiot et al [63] report thermal hypoalgesia 8 weeks post STZ-treatment. IENF density [62] and MFD [65] are reduced in diabetic Swiss mice, as is nerve blood flow, levels of nerve growth factor (NGF) in sciatic nerve and serum, and size of dorsal root ganglia (DRG) neurons [62].…”
Section: Mouse Models Of Dnmentioning
confidence: 99%
“…23 While other methods exist for estimating cellular aging, the G6PD activity in the RBC is of interest due to its reported relationship to diabetic complications through the increased activity of the aldose reductase pathway. [24][25][26] It is reported that inhibition of this pathway with aldose reductase inhibitors such as tolrestat leads to an increase in the activity of the pentose phosphate pathway (and a subsequent increase in G6PD activity) and hence NADPH levels. 27,28 Conversely, activation of the aldose reductase pathway leads to an apparent decrease in pentose phosphate pathway activity, which is associated with a decrease in G6PD activity and, hence, cellular NADPH levels.…”
Section: Introductionmentioning
confidence: 99%
“…The SHD-STZ model exhibits a robust and early neuropathic phenotype, and changes in neuropathic function, including increased thermal latency, decreased mechanical sensitivity, decreased NCV, and decreased IENFD, are typically observed by 12 weeks after STZ administration (Demiot et al 2006;Johnson et al 2008;Muller et al 2008;Obrosova et al 2005). However, the SHD-STZ model is associated with severe toxicity and high levels of postinjection mortality (Ventura-Sobrevilla et al 2011).…”
Section: Streptozotocin-induced Diabetes In Micementioning
confidence: 99%